(untitled) (Horizontes de Enfermería, 2022)
According to the WHO, in 2018, Non-Communicable Diseases (NCDs) killed 41 million people, of which 15 million were “premature” deaths (30 to 70 years); In Ecuador, NCDs occupy the top five causes of mortality, despite being preventable. In this study, the dietary pattern and lifestyle habits were determined as predisposing factors to cardiovascular diseases (CVD) in a sample of 49 adolescents and 241 adults from Chalguayacu - Imbabura. Based on María Teresa Menchú’s Methodologies for Food Consumption Studies, the WHO STEPwise method for monitoring risk factors for chronic diseases, and the National Health and Nutrition Survey (ENSANUT - ECU - 2012), a survey was structured and applied, the results of which highlighted a daily consumption of: vegetable oil, rice, white bread, fruit juices, sugar, and salt. At the frequency of 2 to 4 days/week, most of the other foods were identified, Including: whole milk, regular cheese, eggs, meat, chicken, legumes, greens and vegetables, noodles, bananas, potatoes, coffee, and tea. The adults perceived the quality of their diet as regular, and for the teenagers, it was good. It is concluded that the pattern of consumption and eating habits do not represent a risk for CVD, but the consumption of alcoholic beverages does, having a risk of 24.49% in adolescents and 57.21% in adults; physical inactivity, 95.99% in the entire sample, is another risk factor to consider.